Dopamine sensor based on coreshell poly paraphenylene diamine/ titanium dioxide/ multiwalled carbon nanotube nanocomposite. (2022) - Rajeshwari, V; Vedhi, C; Fernando, Jessica
Abstract: Polymer nanocomposites based on electroactive conducting polymers with nanoparticle fillers have gained a lot of interest in recent years due to their highly desired multifunctional properties. In the diagnosis of many mental illnesses, an accurate and sensitive assessment of dopamine is critical. Because it coexists with other high-concentration biomolecules in biological samples, determining it remains difficult. In this study, p-phenylenediamine was polymerized, and composites were made by magnetic stirring TiO2 and multiwalled carbon nanotube into the polymer. Analytical techniques such as UV–Vis, FT-IR, and FE-SEM examination were used to characterize these nanocomposites. For in vivo detection of dopamine, a new electrochemical biosensor based on poly p-phenylenediamine and titanium dioxide decorated carbon nanotubes was presented. In the detection of dopamine, the constructed sensor has a remarkable sensitivity with a linear range of 3.81 × 10 -11 –4.76 × 10 −6 M and a limit of detection as low as 9.45 × 10 −12 M.